The end of GATT-WTO history? – Reflections on the future of the post-Doha World Trade Organization - Clara Brandi; Matthias Helble (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The prospects for a successful conclusion to the Doha Development Round (DDR) have become bleak. This paper reviews the main reasons for the difficulties that World Trade Organization (WTO) members face in reaching an agreement and argues that, as the DDR is likely to be the last multilateral round of talks on trade liberalisation, it will mark the end of GATT/WTO history as we know it. Against this background, the second part of the paper discusses the future role of the WTO post DDR. We envisage its having five main functions: settling trade disputes, overseeing the international trading system and ensuring it functions smoothly; supporting capacity-building by providing technical assistance, training and Aid for Trade for developing countries; performing a research function and acting as a think-tank on trade; and acting as the key forum for discussions and reflections on all topics related to international trade.
Keywords: 330